Analisis Beban Kerja dan Stres Kerja pada Perawat di Rumah Sakit - Siti Awaliyah Savira Bilqis; Suherman Jaksa; Irna Hasanah (Lembaga Pengembangan Kinerja Dosen, 2025)
In daily life, people often experience stress, whether at work, within the family, or while interacting with other. However, in the workplace, stress becomes a unique challenges, especially for profession with high pressure such a nurses. Nurses often become the group most vulnerable to work-related stress due to the heavy workload and high emotional pressure. This study is a literature review aimed at evaluating and analysis the relationship between nurse work stress and the number of tasks they handle in hospitals. This study examined 15 scientifik journals published from January to april 2025. Most of the research finding indicate that there is a significant relationship between workplace stress and the amount of workload received. The stress levels experienced by nurses usually increase due to excessive workloads, both in terms of the number of takss and the level of difficulty.